An analysis of potential barriers and enablers to regulating the television marketing of unhealthy foods to children at the state government level in Australia - Chung Alexandra; Shill Jane; Swinburn Boyd; Mavoa Helen; Lawrence Mark; Loff Bebe; Crammond Bradley; Sacks Gary; Allender Steven; Peeters Anna (BMC, 2012)
Abstract Background In Australia there have been many calls for government action to halt the effects of unhealthy food marketing on children's health, yet implementation has not occurred. The attitudes of those involved in the policy-making process towards regulatory intervention governing unhealthy food marketing are not well understood. The objective of this research was to understand the perceptions of senior representatives from Australian state and territory governments, statutory authorities and non-government organisations regarding the feasibility of state-level government regulation of television marketing of unhealthy food to children in Australia. Method Data from in-depth semi-structured interviews with senior representatives from state and territory government departments, statutory authorities and non-government organisations (n=22) were analysed to determine participants' views about regulation of television marketing of unhealthy food to children at the state government level. Data were analysed using content and thematic analyses. Results Regulation of television marketing of unhealthy food to children was supported as a strategy for obesity prevention. Barriers to implementing regulation at the state level were: the perception that regulation of television advertising is a Commonwealth, not state/territory, responsibility; the power of the food industry and; the need for clear evidence that demonstrates the effectiveness of regulation. Evidence of community support for regulation was also cited as an important factor in determining feasibility. Conclusions The regulation of unhealthy food marketing to children is perceived to be a feasible strategy for obesity prevention however barriers to implementation at the state level exist. Those involved in state-level policy making generally indicated a preference for Commonwealth-led regulation. This research suggests that implementation of regulation of the television marketing of unhealthy food to children should ideally occur under the direction of the Commonwealth government. However, given that regulation is technically feasible at the state level, in the absence of Commonwealth action, states/territories could act independently. The relevance of our findings is likely to extend beyond Australia as unhealthy food marketing to children is a global issue.